2020
DOI: 10.1002/pc.25714
|View full text |Cite
|
Sign up to set email alerts
|

Prediction on electrical resistivity of thin‐ply unidirectional composites considering electric tunnel effect

Abstract: This article presents a model for equivalent conductive paths to predict the resistivity of thin-ply carbon fiber reinforced unidirectional laminate (UDL), which incorporates electric tunnel effect. A statistical method was used to calculate the effective intra-laminar conductive contact ratio and the number of inter-laminar conductive pathways. Resistivities of four samples with ply thickness varying from 0.02 to 0.1 mm were calculated. A detailed comparison between the predicted and measured resistivities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…PTFE, one of several synthetic polymeric matrices, has excellent corrosion resistance and electrical properties, as well as high temperature resistance and cost-effectiveness [ 1 , 2 ]. Polymers of various forms, particularly fibers influenced by MOs, are frequently used to improve polymer characteristics, resulting in low-cost, high-functioning nano-composites [ 3 , 4 , 5 , 6 ]. Because of the mechanical, physical, and chemical stability of PTFE, it may be utilized as a substrate for the development of ZnO nanotubes, allowing for the effective production of various sensors [ 7 ] and nanoscale photodetectors used for nano optics applications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTFE, one of several synthetic polymeric matrices, has excellent corrosion resistance and electrical properties, as well as high temperature resistance and cost-effectiveness [ 1 , 2 ]. Polymers of various forms, particularly fibers influenced by MOs, are frequently used to improve polymer characteristics, resulting in low-cost, high-functioning nano-composites [ 3 , 4 , 5 , 6 ]. Because of the mechanical, physical, and chemical stability of PTFE, it may be utilized as a substrate for the development of ZnO nanotubes, allowing for the effective production of various sensors [ 7 ] and nanoscale photodetectors used for nano optics applications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in contact angle reduces the water-repellent properties of the material, which can affect its performance in applications such as filtration. In a study [ 62 ], Electrospun Hydrophobic PTFE-NiO Composite was found to have a contact angle of 146° at 20% relative humidity, which increased to 159° at 80% relative humidity. The increase in contact angle at higher relative humidity indicates that the material becomes more hydrophobic with increasing humidity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the study found that thicker mats with a thickness of 30 μm had higher tensile strength compared to thinner mats with a thickness of 10 μm. The higher tensile strength of the thicker mats was attributed to the higher fiber density and interconnectivity of the fibers within the mat [ 47 – 50 , 62 , 63 ]. Nanofiber composite filter mats typically have high air permeability due to the ultrafine fibers used in their construction, which create small pores that allow air to pass through easily.…”
Section: Resultsmentioning
confidence: 99%
“…The electron transport process for conductive fillers is relatively complicated. Currently, there are a few main theories, which are the conductive channel theory, field emission theory, and tunnel effect theory [29,30]. The conductive channel theory is suitable for cases where the concentration of the conductive filler is high, and the conductive particles need to contact each other to realize the propagation of electrons.…”
Section: Antimicrobial Propertymentioning
confidence: 99%